2016
DOI: 10.1186/s13293-016-0060-3
|View full text |Cite
|
Sign up to set email alerts
|

High-fat diet impairs spatial memory and hippocampal intrinsic excitability and sex-dependently alters circulating insulin and hippocampal insulin sensitivity

Abstract: BackgroundHigh-fat diets promoting obesity/type-2 diabetes can impair physiology and cognitive performance, although sex-dependent comparisons of these impairments are rarely made. Transient reductions in Ca2+-dependent afterhyperpolarizations (AHPs) occur during memory consolidation, enhancing intrinsic excitability of hippocampal CA1 pyramidal neurons. In rats fed standard diets, insulin can enhance memory and reduce amplitude and duration of AHPs.MethodsEffects of chronic high-fat diet (HFD) on memory, circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 94 publications
1
13
0
Order By: Relevance
“…Evidence to suggest that the quality of diet and weight having a significant impact on cognition has increased substantially. For example, mice on a high fat diet display increased anxiety-like behavior and impaired learning [2,3]. Similar results can be seen in human populations.…”
Section: Introductionsupporting
confidence: 58%
“…Evidence to suggest that the quality of diet and weight having a significant impact on cognition has increased substantially. For example, mice on a high fat diet display increased anxiety-like behavior and impaired learning [2,3]. Similar results can be seen in human populations.…”
Section: Introductionsupporting
confidence: 58%
“…In fact, the amount of insulin in hippocampus, hypothalamus, and cerebral cortex is 10-100 times that in plasma. Insulin also promotes neuronal cell growth and increases synapse plasticity [36]. Thus, insulin function in the central nervous system is related to homeostasis and proper brain function [5].…”
Section: Discussionmentioning
confidence: 99%
“…Also, it has been shown that mGluRs are involved in various forms of synaptic plasticity in the hippocampus ( Bortolotto et al, 1999 ). Underwood and Thompson have found that HFD significantly reduces hippocampal intrinsic excitability in both young adult male and female Long-Evans rats ( Underwood and Thompson, 2016 ), and activation of group II mGluRs increases the hippocampal network activity ( Ster et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%